2017
DOI: 10.1101/gad.299347.117
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic application of the repressive histone modification H3K9me2 establishes post-zygotic reproductive isolation inArabidopsis thaliana

Abstract: Hybrid seed lethality as a consequence of interspecies or interploidy hybridizations is a major mechanism of reproductive isolation in plants. This mechanism is manifested in the endosperm, a dosage-sensitive tissue supporting embryo growth. Deregulated expression of imprinted genes such as ADMETOS (ADM) underpin the interploidy hybridization barrier in Arabidopsis thaliana; however, the mechanisms of their action remained unknown. In this study, we show that ADM interacts with the AT hook domain protein AHL10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 102 publications
4
64
0
Order By: Relevance
“…However, our results differ in that AHL10 primarily affected growth at low w and in that AHL10 is a member of the less studied Clade B AHLs (AHL1-AHL14). The only other study of AHL10 that we are aware of found AHL10 to be involved in recruitment of the heterochromatin mark Histone 3 Lysine 9 dimethylation (H3K9me2) to ATrich transposable elements (53). We observed mis-regulated expression of several transposons in ahl10-1.…”
Section: The Growth Assays Gene Expression Analysis and Localizationmentioning
confidence: 62%
“…However, our results differ in that AHL10 primarily affected growth at low w and in that AHL10 is a member of the less studied Clade B AHLs (AHL1-AHL14). The only other study of AHL10 that we are aware of found AHL10 to be involved in recruitment of the heterochromatin mark Histone 3 Lysine 9 dimethylation (H3K9me2) to ATrich transposable elements (53). We observed mis-regulated expression of several transposons in ahl10-1.…”
Section: The Growth Assays Gene Expression Analysis and Localizationmentioning
confidence: 62%
“…Alternatively, the doubling of the maternal genome may induce increased maternal loading of PRC2 and lead to a more repressed state of the target sites; paternal genome doubling may have caused titration PRC2 activity via increased copy numbers of the target sites (Kinoshita, ; Kohler et al ., ). In addition to the PRC2 and the type‐I MADS‐box pathway, recent analyses of an interploidy cross in A. thaliana revealed a second molecular pathway for the post‐zygotic hybridization barrier (Jiang et al ., ). In this pathway, the levels of H3K9me2 in the matrix attachment region are high in a cross of female 2x and male 4x A. thaliana ; these high levels are mediated by the paternally expressed ADMETOS gene, the AT‐hook domain protein AHL10 gene and the SUVH9 gene.…”
Section: Discussionmentioning
confidence: 97%
“…However, their level of deregulation remained substantially lower compared to 3x seeds. This data suggest that auxin acts either independently of the pathways previously shown to affect 3x seed abortion (Kradolfer et al, 2013a; Wolff et al, 2015; Jiang et al, 2017) or, alternatively, that auxin signalling is downstream of PEG and AGL functions in the endosperm.…”
Section: Resultsmentioning
confidence: 65%